Serum microRNAs as diagnostic markers of endometriosis: a comprehensive array-based analysis - Cosar, Emine; Mamillapalli, Ramanaiah; Ersoy, Gulcin Sahin; Cho, SihYun; Seifer, Benjamin; Taylor, Hugh S (Fertility and sterility, 2016)
To investigate serum microRNAs (miRNAs) in women with endometriosis. Case-control study. University hospital. Women with (n = 24) and without (n = 24) endometriosis. Serum samples were obtained from surgically diagnosed subjects. miRNA from women with without endometriosis were used for microarray profiling and confirmed by means of quantitative real-time polymerase chain reaction (qRT-PCR). Receiver operating characteristic (ROC) analysis was performed on differentially expressed miRNAs. miR-3613-5p, miR-6755-3p were down-regulated and miR-125b-5p, miR-150-5p, miR-342-3p, miR-143-3p, miR-145-5p, miR-500a-3p, miR-451a, miR-18a-5p were up-regulated more than 10-fold in the microarray. These results were confirmed with the use of qRT-PCR. Among the differentially expressed miRNAs, miR-125b-5p expression levels had the highest area under the ROC curve (AUC). The maximum AUC score of 1.000 was achieved when combining miR-125b-5p, miR-451a, and miR-3613-5p with the use of a logistic regression model. We identified several miRNAs in serum that distinguished subjects with endometriosis from those without. miR-125b-5p had the greatest potential as a single diagnostic biomarker. A combination of that miRNA with miR-451a and miR-3613-5p further improved diagnostic performance.